Phytosociology of weeds associated with carrot crops in two municipalities of boyacá - Cordoba Patiño, Luis David; Pinzón-Sandoval, Elberth Hernando (Universidad Pedagógica y Tecnológica de Colombia, 2021)
In order to know the phytosociology of the weeds associated with a carrot crop (Daucus carota L.) under conditions of the municipalities of Ventaquemada and Jenesano-Boyacá, a lot was selected per municipality for carrot cultivation and a plot was made W-shaped covering an area of ​​500 m2. Relative density, relative frequency, relative dominance and the importance value index (IVI) were calculated, as well as the Alpha and Beta diversity indices for the sampled areas. A total of 6 families and 11 species were counted, of these 63.64% were represented by annual plants and 36.36% by perennial plants. The class Liliopsida (Monocotyledonous) was represented by the family Poaceae. While the Magnoliopsida (Dicotyledonous) class was represented by the families: Asteraceae, Brassicaceae, Boraginaceae, Leguminosaceae, Polygonaceae, the latter being the one that contributed the largest number of species. The species R. crispus and P. nepalense were those that presented the highest values ​​of Importance value index (IVI) with 0.953 and 0.959, respectively. Accordingly, with the Shannon-Wiener diversity index and Simpson dominance, the evaluated areas presented a low species diversity and a high probability of dominant species. The results found can serve as a basis and tool for the carrot producers in the evaluated areas, to define the management plans of the associated weeds and thus optimize the yields in this crop.